Economic openness and trade policy: Struggles of the dairy sector in colombia [Apertura económica y política comercial: Estudio del sector lácteo y sus dificultades en colombia] (2020)
Since the economic openness in Colombia, some economic sectors have experienced significant challenges to compete with foreign products, as is the case of the dairy sector. Thus, this article provides an analysis between economic openness and the behavior of the dairy sector in Colombia, considering that many products in this industry have applied prohibitive custom rates and bound tariffs, making the dairy sector the one with the highest level of tariff protectionism. Therefore, variables such as exports, imports, productive capacity, consumption, among others, were analyzed at the national level and in Latin America-The Caribbean. The results show that in Colombia there are excessive levels of tariff protectionism and a growth in imports in the dairy sector, reflecting internal problems of productive efficiency and competitiveness. In conclusion, it is proposed to focus Colombian exports on products with higher added value and continue with the efforts to modernize and capitalize the dairy supply chain, to offer competitive national prices and satisfy domestic demand. © 2020, Universidad del Zulia. All rights reserved.